2018
DOI: 10.1111/jfb.13632
|View full text |Cite
|
Sign up to set email alerts
|

Swimming performance of 12 Schizothoracinae species from five rivers

Abstract: A series of stepped velocity tests were carried out in a Brett-type swimming respirometer and the overall range in swimming performance for 12 Schizothoracinae species was measured. The relative critical swimming speed U and burst speed U decreased with body length, while absolute U and U increased with body length. U increased with temperature up to approximately 15 C and then decreased. Species with a high U also displayed a higher U .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
3
3
0
Order By: Relevance
“…black carp: The fish with different body lengths have different fish swimming abilities. Some studies have reported that they were the linear correlation between fish swimming speed and body length [16,[20][21][22]. In this study, it can be seen from Figure 3 that the swimming speed (critical and burst swimming speed) (m/s) of the four carps increased with the increased body length, and the relative (critical and burst) swimming speed (BL/s) decreases with body length, which is similar to previous research results.…”
Section: Burst Swimming Speedsupporting
confidence: 90%
See 1 more Smart Citation
“…black carp: The fish with different body lengths have different fish swimming abilities. Some studies have reported that they were the linear correlation between fish swimming speed and body length [16,[20][21][22]. In this study, it can be seen from Figure 3 that the swimming speed (critical and burst swimming speed) (m/s) of the four carps increased with the increased body length, and the relative (critical and burst) swimming speed (BL/s) decreases with body length, which is similar to previous research results.…”
Section: Burst Swimming Speedsupporting
confidence: 90%
“…The water velocity was initially set at 1 BL/s, and increased by specified time intervals (∆t) until the fish ceased swimming for 5s and was considered exhausted [7,15,16]. U crit and U burst were identified by conducting increasing velocity tests and were calculated using the formula described by Brett (1964), as follows:…”
Section: Test Methodsmentioning
confidence: 99%
“…As has been previously reported in several studies of freshwater sh(Cai et al 2020;Starrs et al 2011;Zupa et al 2015), at a given temperature, critical velocity increased as the studied species L T increased. There was a linear relationship between critical velocity and L T , similar to what was reported byHou et al (2018). Thus, sh L T is relevant when estimating critical velocity (Table5and 6), increasing at larger sizes as has been observed in many studies(Mateus et al.…”
supporting
confidence: 85%
“…The relationships between the escape speed of fish and other classic fish swimming speeds (e.g., critical swimming speed, U c and burst swimming speed, U b ) measured in swim chambers or open channels (Katopodis, Cai, & Johnson, 2019; Katopodis & Gervais, 2016) may assist in quantifying the ability of fish to escape accelerating flows. The data of U c and U b were obtained using the stepped‐velocity and fixed‐velocity (Hou et al, 2018) tests, respectively, in a Loligo System (http://www.loligosystems.com). The critical swimming speed was measured by gradually increasing the water velocity in 20‐min time step and the burst swimming speed was measured at the time to fatigue for a fixed water velocity.…”
Section: Methodsmentioning
confidence: 99%